PRAGMATIC FUNCTION OF NUMERIC IDEOGRAPHIC SYMBOLS AT LIAISON INTERPRETING - Hunchyk, І. О.; Voloshyn, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the pragmatic function of numeric ideographic symbols within the framework of liaison interpreting. Some close attention is focused on the primary and secondary codifications of numbers from 0 up to 10 in French phraseological units, conversational and secret messages. The relevance of numeric ideographic symbols is demonstrated accordance to their meanings and pragmatic functions at oral liaison interpreting.